PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP MINAT BELAJAR DAN PENGUASAAN KONSEP FISIKA PADA PESERTA DIDIK KELAS VII SMP NEGERI 26 MAKASSAR - Nardin, Nardin; Tawil, Muhammad (Jurnal Sains dan Pendidikan Fisika, 2016)
The study almed at (1) desribling the students? learning interst on Physics taught by employing problem-based learning model, (2) desribling the mastery of Physics concept taught by employing problem-based learning model, (3) desribling the mastery of Physics concept taught by employing discovery learning model, (4) desribling the mastery of Physics concept taught by employing discovery learning model, (5) analyzing the students? learning interest on Physics taught by employing problem-based learning model and the one with discovering learning model, (6) analyzing the mastery of Physics concept taught by employing problem-based learning model and the one with discovery learning model. The study employed experiment research with posttest only control design. The population of the study was all class VII students at SMPN 26 Makassar consisted of nine class with the total 270 students. The samples were two classes, class VII4 as the experiment class taught by employing problem based learning model and class VII5 as the control class taughtby employing conventional learning model with 29 students in each class, obtained by employing random sampling technique. The results of the study reveal that (1) the students? learning interest on Physics taught by employing problem based learning model with the indicators of favorite, interest, attention, and involvement is in high category, (2) the students? learning interest on hysics taught by employing discovey learning model with the indicators of favorite, interest, attention, and involvement is in low score, (3) the mastery of Physics concept of syudents taught by employing problem based learning model is in very high category, (4) the mastery of Physics concept of syudents taught by employing discovery learning model is in very high category, (5) the students? learning interest on hysics taught by employing problem based learning is higher than the one taught by employing discovery learning model, and (6) the mastery of Physics concept of syudents taught by employing problem based learning model is higher than the one taught by employing discovery learning model. Keywords: discovery learning, interest, learning outcomes Penelitian ini bertujuan untuk: (1) mendeskripsikan minat belajar fisika peserta didik yang diajar dengan model pembelajaran berbasis masalah, (2) mendeskripsikan penguasaan konsep fisika peserta didik yang diajar dengan model pembelajaran berbasis masalah, (3) mendeskripsikan minat belajar fisika peserta didik yang diajar dengan model pembelajaran discovery learning, (4) mendeskripsikan penguasaan konsep fisika peserta didik yang diajar dengan model pembelajaran discovery learning, (5) menganalisis minat belajar fisika peserta didik yang diajar dengan model pembelajaran berbasis masalah dan peserta didik yang diajar dengan model pembelajaran discovery learning, (6) menganalisis penguasaan konsep fisika peserta didik yang diajar dengan model pembelajaran berbasis masalah dan peserta didik yang diajar dengan model pembelajaran discovery learning. Jenis penelitian yang dipilih adalah penelitan eksperimen dengan desain posttest only control group design. Penelitian ini menggunakan dua kelas yaitu kelas eksperimen yang diajar dengan model pembelajaran berbasis masalah dan kelas kontrol dengan pembelajaran discovery learning. Populasi dalam penelitian ini adalah seluruh peserta didik kelas VII SMP Negeri 26 Makassar terdiri dari sembilan kelas dengan jumlah keseluruhan peserta didik 270 orang, sedangkan sampel diambil dengan teknik pengacakan kelas sehingga terpilih Kelas VII4 sebagai kelas eksperimen dan Kelas VII5 sebagai kelas kontrol dengan jumlah sampel masing-masing 29 orang. Hasil penelitian menunjukkan bahwa (1) minat belajar fisika yang diajar dengan model pembelajaran berbasis masalah pada peserta didik dengan indikator kesukaan, ketertarikan, perhatian, dan keterlibatan berada pada skor tinggi, (2) minat belajar fisika yang diajar dengan model pembelajaran discovery learning peserta didik dengan indikator kesukaan, ketertarikan, perhatian, dan keterlibatan berada pada skor rendah , (3) penguasaan konsep fisika yang diajar melalui model pembelajaran berbasis masalah berada pada kategori sangat tinggi, (4) penguasaan konsep fisika yang diajar melalui pembelajaran model discovery learning peserta diidk berada pada kategori tinggi, (5) minat belajar peserta didik dengan model pembelajaran berbasis masalah lebih tinggi daripada peserta didik yang diajar dengan model pembelajaran discovery learning dan, (6) penguasaan konsep fisika peserta didik dengan model pembelajaran berbasis masalah lebih tinggi daripada peserta didik yang diajar dengan model pembelajaran discovery learning. Kata Kunci: hasil belajar, minat, pembelajaran berbasis masalah